2022
DOI: 10.2147/ijgm.s349846
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Analysis of Carotid Stenosis Among Ischaemic Heart Diseases Patient in Bangladesh: A Cross-Sectional Study

Abstract: Purpose This study aimed to evaluate the prevalence of carotid stenosis among ischaemic heart disease (IHD) patients undergoing coronary artery bypass graft (CABG) surgery and identify risk factors associated with carotid stenosis at a tertiary-level hospital in Bangladesh. Patients and Methods This cross-sectional study examined 200 IHD patients scheduled for isolated and elective CABG surgery, and multivariate regression analysis was used to determine the impact of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 21 publications
6
12
0
Order By: Relevance
“…Several studies reported the risk factors of significant CAS, such as a history of cerebrovascular accident, diabetes mellitus, hypertension, dyslipidemia, and obesity [10][11]17]. Our study demonstrates a positive relationship between age and the severity of CAS, with older patients displaying a significant association (p < 0.001).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Several studies reported the risk factors of significant CAS, such as a history of cerebrovascular accident, diabetes mellitus, hypertension, dyslipidemia, and obesity [10][11]17]. Our study demonstrates a positive relationship between age and the severity of CAS, with older patients displaying a significant association (p < 0.001).…”
Section: Discussionsupporting
confidence: 54%
“…However, Ranjan et al (2022) found the overall prevalence of CAS to be 13% lower than the findings in our study. This study contrasts with the aforementioned study, in which there were specific selection criteria and the prevalence of CAS was only found in patients undergoing CABG, with other types of cardiac surgery excluded [11].…”
Section: Discussionmentioning
confidence: 69%
“…Following cardiac surgery, pain disrupts the humoral and neuroendocrine systems' equilibrium, increasing stress hormone levels and myocardial oxygen demand. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 As a result, arrhythmias and myocardial ischemia are increased. Pain also impairs mechanical ventilation and mobility restriction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Oxygen supply‐demand mismatch can lead to myocardial ischemia, detrimental to patient outcomes. 7 , 8 Optimal postoperative pain management with a regular and routine assessment of pain will improve postoperative outcomes. The patient's assessment of pain using a visual analog scale (VAS) is the most reliable and should be used when possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation